Shame : a novel - Nāsarina, Tasalimā (Prometheus Books, 1997)
The animosity and bloodletting between Muslim and Hindu extremists on the Indian subcontinent are centuries old. But when the 450-year-old Babri mosque in Ayodhya (southeast of Delhi) was destroyed by Hindu fundamentalists in 1992, it let loose a worldwide wave of Muslim reprisals against all Hindus - a reign of terror that extended even to Bangladesh's small Hindu community.